Association of blaCTX-M-15 and qnr genes in multidrug-resistant Salmonella Typhimurium and Shigella spp from India - Dhiviya Prabaa Muthuirulandi Sethuvel; Shalini Anandan; Naveen Kumar Devanga Ragupathi; Balaji Veeraraghavan; Ohri Vinod; Kamini Walia (Journal of Infection in Developing Countries)
This item has no abstract. Follow the links below to access the full text.